1960
DOI: 10.1161/01.res.8.6.1187
|View full text |Cite
|
Sign up to set email alerts
|

Dicumarol Therapy

Abstract: One of the problems of Dicumarol administration has been determination of the adequacy of therapy. A fundamental stage in thrombus formation in the circulation is platelet clumping. Since platelets are involved in both hemostasis and thrombosis, a study of changes in platelet function may prove useful. The effects of Dicumarol on platelet clumping and adhesiveness have, therefore, been studied and related to changes in other clotting mechanisms. Comparison of platelet function in control periods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1962
1962
1979
1979

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…If, indeed, smoking affects the arterial wall or endothelium, or blood coagulation, we might reasonably expect this to be reflected in the survival of the blood platelets. The greater part of the evidence indicates that diet influences in vitro tests of blood coagulation (Mustard, 1961), and we have recently shown that this is also true of platelet survival (Mustard and Murphy, 1962). It is therefore clearly important that studies such as the one reported in this paper should be done under *This study was supported in part by United States Public Health Grant H-4964, a grant from the Department of Veterans Affairs, and a grant from the Armour Pharmaceutical Company.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…If, indeed, smoking affects the arterial wall or endothelium, or blood coagulation, we might reasonably expect this to be reflected in the survival of the blood platelets. The greater part of the evidence indicates that diet influences in vitro tests of blood coagulation (Mustard, 1961), and we have recently shown that this is also true of platelet survival (Mustard and Murphy, 1962). It is therefore clearly important that studies such as the one reported in this paper should be done under *This study was supported in part by United States Public Health Grant H-4964, a grant from the Department of Veterans Affairs, and a grant from the Armour Pharmaceutical Company.…”
mentioning
confidence: 85%
“…The techniques involved have already been described in detail (Murphy and Mustard, 1960). Samples of blood were taken daily during the 10-day period in which platelet survival was studied.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations